ANALISIS TINGKAT KESELAMATAN TOL CIKAMPEK – PALIMANAN (CIPALI) MENGGUNAKAN ROAD HAZARD MAPPING (RHM) - Anita Juraida; Nova Indah Saragih; Ayu Endah Wahyuni; Iqbal Yulizar Mukti; Oktri Mohammad Firdaus (PROCEEDING STIMA)
The growth rate of four-wheeled vehicles in particular increased significantly each year. This is supported by several aspects of which increase people's purchasing power, the rate of population mobility is increasing, and they still lack the means of public transport that is safe, convenient and timely. Since 2015 the government has been operating new Toll Road from Cikampek to Palimanan (CIPALI) which aims to reduce number of congestion on the northern coast line, especially in the holiday season of Eid. This study aimed to analyze the level of safety Cipali toll road using a Road Hazard Mapping (RHM). The method used is a combination of direct observation data collection and analysis via Google Maps. The results of the study obtained a draft RHM which can be used as a reference for the driver before entering the Cipali toll both from Cikampek to Palimanan and vice versa.Keywords: safety driving, cipali, road hazard mapping (RHM)